2006
DOI: 10.1007/s10863-006-9006-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Kinetic Characterization of HtDTC, The Mitochondrial Dicarboxylate–Tricarboxylate Carrier of Jerusalem Artichoke Tubers

Abstract: Jerusalem artichoke (Helianthus tuberosus L.) tubers were reported to be tolerant to cold and freezing. The aim of this study was to perform a kinetic characterization of the mitochondrial dicarboxylate-tricarboxylate carrier (HtDTC) and to assess a possible involvement of this carrier in the cold tolerance of tubers. The HtDTC was purified from isolated mitochondria by sequential chromatography on hydroxylapatite/celite and Matrex Gel Orange A. SDS gel electrophoresis of the purified fraction showed a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The purity of the mitochondrial preparations was checked by assaying marker enzymes as reported in ''Materials and methods''. In accordance with the data of Spagnoletta et al (2006) this analysis showed that extramitochondrial contamination was negligible (data not shown). To monitor DW, we used safranin O as a fluorescence probe as reported in ''Materials and methods'' (Table 1).…”
Section: Assessment Of Jam Integrity Functionality and Hplc Measuremsupporting
confidence: 91%
See 1 more Smart Citation
“…The purity of the mitochondrial preparations was checked by assaying marker enzymes as reported in ''Materials and methods''. In accordance with the data of Spagnoletta et al (2006) this analysis showed that extramitochondrial contamination was negligible (data not shown). To monitor DW, we used safranin O as a fluorescence probe as reported in ''Materials and methods'' (Table 1).…”
Section: Assessment Of Jam Integrity Functionality and Hplc Measuremsupporting
confidence: 91%
“…The purity of the mitochondrial preparations was checked by assaying marker enzymes for endoplasmic reticulum, peroxisomes, plasma membranes, and vacuoles, as described in Spagnoletta et al (2006).…”
Section: Isolation Of Jammentioning
confidence: 99%
“…Unlike the other three highly abundant MC proteins: ADP/ATP carriers (AtAAC1-3; 6.2% of IMM area; 53,065 protein copies/mitochondria); mitochondrial phosphate carriers (AtMPT2-3; 2.5% of IMM area; 21,325 protein copies/mitochondria); and, uncoupling proteins (AtUCP1-3, 1.0% of IMM area; 8595 protein copies/mitochondria), there is only one DTC homolog in Arabidopsis. DTCs have been studied in a few plants including Arabidopsis and Nicotiana tabacum [48], Vitis vinifera (grapes) [49], Helianthus tuberosus (Jerusalem artichoke) [50], and Citrus junos (yuzo) [51]. The purification and characterization of a citrate transporter in maize have been described [52].…”
Section: Dicarboxylate/tricarboxylate Carrier (Dtc)mentioning
confidence: 99%
“…Two mitochondrial carrier proteins (i.e., dicarboxylate/tricarboxylate carrier (DTC) and 2-oxoglutarate/malate carrier protein (OMC)) were decreased in T. aestivum [35] and G. max [17], respectively. DTC and OMC can catalyze the transport of various metabolites (e.g., dicarboxylates, tricarboxylates, amino acids, and keto acids) across the inner mitochondrial membrane, and play an important role in several metabolic processes, such as the gluconeogenesis, nitrogen metabolism, as well as biotic stress [178]. However, three voltage-dependent anion channel proteins (VDAC) in T. aestivum [35] and two mitochondrial outer membrane porin 1-like proteins in B. napus [47] were significantly increased under drought stress.…”
Section: Membrane Traffickingmentioning
confidence: 99%